18h*483=462*21h

Simple and best practice solution for 18h*483=462*21h equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18h*483=462*21h equation:


Simplifying
18h * 483 = 462 * 21h

Reorder the terms for easier multiplication:
18 * 483h = 462 * 21h

Multiply 18 * 483
8694h = 462 * 21h

Multiply 462 * 21
8694h = 9702h

Solving
8694h = 9702h

Solving for variable 'h'.

Move all terms containing h to the left, all other terms to the right.

Add '-9702h' to each side of the equation.
8694h + -9702h = 9702h + -9702h

Combine like terms: 8694h + -9702h = -1008h
-1008h = 9702h + -9702h

Combine like terms: 9702h + -9702h = 0
-1008h = 0

Divide each side by '-1008'.
h = 0

Simplifying
h = 0

See similar equations:

| 6(3N-1)=-96 | | 3y+5y=64y | | 7y+7=6r+12 | | 12a^5+30a^3-30a=0 | | 4(y-1)+y=2y+20 | | 42x+42=42x+42 | | 3+5u=98 | | 4(y+5)-24=0 | | 5(x+8)-9= | | 6(T+2)+3(3-5T)=10(T-4)-6 | | 11x+9=8x | | 15=5x-3 | | x^2+9x-21=0 | | 7x-6-3x=10 | | -3(x-2)=-15 | | -6(3x*-8)= | | 12x^2+2x-4=o | | 7(3k+4)-18k=64 | | 6=.5m-5 | | 15(b+2)=90 | | -6(3*-8)= | | -12+9=m-2 | | 2x^2+3x-36=0 | | 2k-8=13+5k | | 5z+9=3z-1 | | x-.3x=50 | | 10d=-34-5d | | x-16=25 | | 2v+18=6-4(v-17) | | 19.5+0.5=10.6206-0.4t | | 24-5*3/8-5= | | -13=-4(4)+3 |

Equations solver categories